Teaching for Extrinsic Motivation: AEC644/WC307, 6/2018 - Damiani, Isabella; Thoron, Andrew C.; Bunch, James C. (EDIS, 2018)
Motivation is the idea of being moved to do something, and levels of motivation vary among every individual. Extrinsic motivation is a specific type of motivation that is fueled by external rewards or an expected outcome. This 2-page document, written by Isabella Damiani, Andrew Thoron, and J. C. Bunch and published by the UF/IFAS Department of Agricultural Education and Communication, discusses how educators can foster extrinsic motivation among their students. http://edis.ifas.ufl.edu/wc307